Stress at School? A Qualitative Study on Illegitimate Tasks during Teacher Training - Faupel, Stefanie; Otto, Kathleen; Krug, Henning; Kottwitz, Maria U. (Frontiers in Psychology, 2016)
What do I expect when stating that “I am going to be a teacher”? Social roles, including professional roles, often become part of people's identity and thus, of the self. As people typically strive for maintaining a positive sense of self, threats to one's role identity are likely to induce stress. In line with these considerations, Semmer et al. recently (e.g., Semmer et al., 2007, 2015) introduced “illegitimate tasks” as a new concept of stressors. Illegitimate tasks, which are defined as unnecessary or unreasonable tasks, threaten the self because they signal a lack of appreciation regarding one's professional role. Teacher training is a phase of role transition in which the occurrence of illegitimate tasks becomes likely. A holistic understanding of these tasks, however, has been missing up to now. Is there already a professional role identity during teacher training that is vulnerable to threats like the illegitimacy of tasks? What are typical illegitimate tasks in the context of teacher training? In order to close this research gap, 39 situations taken from 16 interviews with teaching trainees were analyzed in the present study on the basis of qualitative content analysis. Seminars and standing in to hold lessons for other teachers were identified as most prevalent illegitimate tasks. More specifically, unnecessary tasks could be classified as sub challenging, inefficient and lacking in organization (e.g., writing reports about workshops no one will ever read). Unreasonable tasks appeared overextending, fell outside responsibility, and lacked supervisory support. Training interventions focusing upon task design and supervisory behavior are suggested for improvement.